2014
DOI: 10.1101/gr.176107.114
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the RNA editomes of wild-type C. elegans and ADAR mutants

Abstract: RNA editing increases transcriptome diversity through post-transcriptional modifications of RNA. Adenosine deaminases that act on RNA (ADARs) catalyze the adenosine-to-inosine (A-to-I) conversion, the most common type of RNA editing in higher eukaryotes. Caenorhabditis elegans has two ADARs, ADR-1 and ADR-2, but their functions remain unclear. Here, we profiled the RNA editomes of C. elegans at different developmental stages of wild-type and ADAR mutants. We developed a new computational pipeline with a ''bisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 52 publications
11
105
3
Order By: Relevance
“…Prior to this study, only 10 hyperedited substrates were known in C. elegans (Morse and Bass 1999;Morse et al 2002), although studies have identified transcripts with multiple editing sites (Wu et al 2011;Washburn et al 2014;Zhao et al 2015). Our final list of 664 GNUMAP +Repeat EERs extends this list considerably.…”
Section: Eers Represent Dsrna Structuresmentioning
confidence: 87%
See 1 more Smart Citation
“…Prior to this study, only 10 hyperedited substrates were known in C. elegans (Morse and Bass 1999;Morse et al 2002), although studies have identified transcripts with multiple editing sites (Wu et al 2011;Washburn et al 2014;Zhao et al 2015). Our final list of 664 GNUMAP +Repeat EERs extends this list considerably.…”
Section: Eers Represent Dsrna Structuresmentioning
confidence: 87%
“…Nonsynonymous editing of codons, which is known to have important functions in other organisms (Bass 2002;Nishikura 2010), although rare, has recently been observed in C. elegans transcripts (Washburn et al 2014;Zhao et al 2015). To determine whether any sites, both inside EERs and outside, resulted in nonsynonymous codon changes, we used the program Annovar to annotate all observed A-to-G changes in coding exons (Wang et al 2010).…”
Section: Nonsynonymous Codon Changes Resulting From Editing Are Absentmentioning
confidence: 99%
“…In C. elegans , the RNA editomes of wild‐type and ADAR mutants were profiled. Worms lacking RNA editing were short‐lived, potentially due to alteration of the abundance of proteins, as determined by quantitative proteomics (Zhao et al, 2015). In AD, RNA editing was studied in a site‐specific manner (Gaisler‐Salomon et al, 2014; Khermesh et al, 2016).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…A recent estimate using multiple strains uncovered ∼50 (Danecek et al, 2012), 34 of which are conserved across mammals (Pinto et al, 2014). In C. elegans, only eight recoding sites were identified (Zhao et al, 2014). In leaf-cutter ants there are thousands of sites, many of which are caste-specific; however, only 57 sites recode and in the diamondback moth there were 152 recoding sites .…”
Section: Adars Do Much More Than Alter Codonsmentioning
confidence: 99%